The Comparison of Three Different Methods on Extraction of Cigarette Butt as Natural Insecticide - Syadza Firdausiah; Firdaus; Hamdayanty; Taufik Hidayat; Muhammad Alfliadhi (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2020)
Background: Cigarette butt could be used as an insecticide due to the present of alkaloid compounds in high yield, especially nicotine and eugenol. To maximize the extraction process of cigarette butt, the study related to the effect of extraction method to the effectivity of extraction process should be performed. Objective: The main purpose of this study was to identify the effect of extraction methods on the total yield and the nicotine and eugenol content of the extract of cigarette butt. Methods: In this study, maceration (CB-1), soxletation (CB-2), and microwave-assisted extraction (MAE) (CB-3) methods were conducted and compared the yield and the nicotine and eugenol content of the extracts by LC-MS. Results: The results showed that the extract CB-3 has the highest yield (26,77%), which compared to CB-1 and CB-2, which are 11.72% and 14.56%, respectively. Furthermore, the nicotine content of all extracts are 54.15%, 36.43%, and 48.51% for extract CB-1, CB-2, and CB-3, respectively, while eugenol content of CB-1, CB-2, and CB-3 are 5.09%, 6.35%, and 8.41%, respectively. Conclusion: Based on the results, it can be concluded that MAE method was more effective to extract the cigarette butt compared to maceration and soxletation method. This method was also reduced the time consuming and the volume of the solvent used in the extraction process which follow green chemistry rule. Thus, MAE method is potential to be used in extraction process of cigarette butt in order to produce a biopesticide.